Engagement in student organizations and graduates’ readiness to enter the job market - Mulyana, Baiq Sinar; Linando, Jaya Addin (Asian Management and Business Review, 2024)
Studies highlight particular concern about the work readiness of university graduates, which potentially leads to many undesirable outcomes, such as rising unemployment rates and low productivity levels in the workplace. This study aims to explore the differences between student organization and work experiences and further analyze student organization’s contribution to graduate’s work readiness. This research uses a qualitative approach with phenomenological methods, and the data is analyzed with thematic data analysis. Data were collected through interviews involving 15 recent graduates actively involved in student organizations and just starting their careers. The study also interviewed two more senior workers to serve as source triangulation, strengthening the validity of the collected data. The study found four key differences between student organizations and the world of work. These differences include primary orientation, feedback and reward system, hierarchical structure, and interaction experiences. The findings also indicate that student organization experiences enhance individual skill development, which later proves helpful in work life. In particular, student organizational experience significantly advances these skills: leadership, time management, self-confidence, problem-solving, integrity, critical thinking, communication, negotiation, teamwork, responsibility, and commitment. Additionally, the record of student organizational participation listed on curriculum vitae can be a valuable asset for recent graduates, enhancing their employment prospects.